Long non-coding RNA HOTTIP promotes prostate cancer cells proliferation and migration by sponging miR-216a-5p. Issue 5 (28th September 2018) - Yang, Bin; Gao, Ge; Wang, Zhixin; Sun, Daju; Wei, Xin; Ma, Yanan; Ding, Youpeng
Abstract : Long non-coding RNAs (lncRNAs) are a class of ncRNAs with >200 nts in length that regulate gene expression. The HOXA transcript at the distal tip (HOTTIP) lncRNA plays an important role in carcinogenesis, however, the underlying role of HOTTIP in prostate cancer (PCa) remains unknown. The aim of the present study was to evaluate the expression and function of HOTTIP in PCa. In the present study, we analyzed HOTTIP expression levels of 86 PCa patients in tumor and adjacent normal tissue by real-time quantitative PCR (qPCR). Knockdown or overexpression of HOTTIP was performed to explore its roles in cell proliferation, migration, invasion, and cell cycle. Furthermore, bioinformatics online programs predicted and luciferase reporter assay were used to validate the association of HOTTIP and miR-216a-5p in PCa cells. Our results found that HOTTIP was up-regulated in human primary PCa tissues with lymph node metastasis. Knockdown of HOTTIP inhibited PCa cell proliferation, migration, and invasion. Overexpression of HOTTIP promoted cell proliferation, migration, and invasion of PCa cells. Bioinformatics online programs predicted that HOTTIP sponge miR-216a-5p at 3′-UTR with complementary binding sites, which was validated using luciferase reporter assay. HOTTIP could negatively regulate the expression of miR-216a-5p in PCa cells. Above all, the knockdown of HOTTIP could represent a rational therapeutic strategy for PCa.